(untitled) (Revista de Estudos da Linguagem, 2025)
Linguistics consolidated itself as an independent science in the last century, being shaped by different approaches. During the modern era, promising trends, such as North American structuralism and generative theory, began to adopt methods and conceptual structures that brought them closer to the natural sciences, especially under the influence of positivism. However, a significant change has been observed in the epistemological panorama of linguistics, driven by the values of postmodernity. This new perspective shakes up truths previously considered absolute and proposes an alternative way of thinking about linguistic phenomena, for which Complexity Theory may account. In this new scenario, conceptually vast and endowed with transdisciplinarity, attention turns to diversity, flexibility and the influence of external factors on language structure and functioning. In this article, we offer epistemological considerations on the trajectory of linguistics in modernity (focusing on both the Bloomfieldian and the Chomskyan enterprises) and in postmodernity (addressing the perspective of complexity) and how this path relates to the construct of science in light of the entities and events of language. This objective is justified by the ability of Complexity Theory to embrace instability, unpredictability and heterogeneity as constitutive elements of language, using an ecological, non-linear and multidimensional view of linguistic phenomena and processes.